A strange antiferromagnetic phase has controlled the magnetic and paleomagnetic properties of the Fe-Ti inversion spinel bearing rocks on the whole Earth globe - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2014)
The magnetic characteristics of Fe and Fe-Ti magnetic mineral bearing rocks of young, through recent, quaternary, mesozoic to palaeozoic age have been studied. I have discovered a strange antiferromagnetic phase (AFMP) in Fe and Fe-Ti magnetic minerals of about 288 samples from 78 localities of volcanic rocks and of about 346 samples of the sedimentary rocks. The AFM phase has played a very important role in magnetism and paleomagnetism of rocks. I have considered that an evolution of the AFM phase started probably after solidification of magnetic minerals during post magmatic process and it has gradually followed during survival of minerals on the Earth’s surface. The AFMP can be found in different evolutional stages, from a begining stage to completely developed stage. The indicated AFMP has the N´eel temperature (TN), in the range from 350 °C to 485 °C, mostly around 450 °C in the samples under study. I have deduced that one can find the rocks in the two basically different aggregations: 1) The rocks containing so called the pseudo original phase state magnetic minerals, where the AFM phase is absent, and 2) The rocks containing the transformed phase state magnetic minerals, where the AFM phase is present. The AFM phase coexists with the ferrimagnetic phases in large range of temperatures and disappears at TN. The AFM phase has a strong relations with magnetic properties, including the polarity of RM of rocks. The rocks with a copletely develped AFM phase have always reversed RM. The AFM phase bearing rocks have possessed lower values of magnetic susceptibility (κ) comparing them with the Fe and Fe-Ti minerals bearing rocks, where the AFMP is absent.